Integrated WHT- and DFT-Based Multiuser Massive MIMO System for Secure RIS-Enabled mmWave Communications - Md. Najmul Hossain; Md. Rakibul Islam; S. K. Tamanna Kamal; Atia Kaniz; Shaikh Enayet Ullah; Tetsuya Shimamura (IEEE Access)
Enhancing signal quality by reducing multiuser interference (MUI), improving system energy efficiency and spectrum efficiency, minimizing interference with adjacent frequency bands, and ensuring secure data communication are critical challenges in the development of future-generation reconfigurable intelligent surface (RIS)-enabled wireless communication systems. To address these challenges and to provide effective solutions, we propose a novel integrated Walsh-Hadamard transform (WHT)- and discrete Fourier transform (DFT)-based multiuser massive multiple-input multiple-output (mMIMO) system for secure RIS-enabled millimeter-wave (mmWave) communications. The proposed system emphasizes more appropriate performance metrics for a standard assumed scenario involving four users for color image transmission. The system integrates a two-dimensional (2D) hyperchaotic system for physical layer security (PLS) encryption, block diagonalization (BD) precoding, repeat-accumulate (RA) channel coding utilizing Cholesky decomposition-based zero-forcing (CD-ZF), and minimum mean square error (MMSE) signal detection techniques. PLS encryption based on a 2D hyperchaotic system significantly improves the confidentiality of the color image signal transmission. BD precoding minimizes multiuser interference, and using integrated WHT- and DFT-based algorithms with null carriers effectively reduces the out-of-band (OOB) spectrum power. The simulation results confirm the effectiveness of the proposed system for PLS enhancement in transmitting color images, demonstrating low image structural similarity indices of −7.70%, −4.82%, −5.48%, and −6.46% for users 1, 2, 3, and 4, respectively, along with an achievable OOB power emission of 312 dB. The four users achieved a bit error rate (BER) of $1× 10^{-3}$ using RA channel coding, MMSE, and 4-QAM digital modulation at a signal-to-noise ratio (SNR) of 20 dB.